Investigations of aging behaviour for aluminium powders during an atmosphere simulation of the LBM process. (27th May 2017) - Bauer, Dominik M.; Schwarzenböck, Elisabeth; Ludwig, Ina; Schupp, Norbert; Palm, Frank; Witt, Gerd
ABSTRACT: Additive layer manufacturing (ALM) offers for production of parts and components for aeronautical applications potential cost benefits over conventional manufacturing routes. In particular, powder bed processes offer a high degree of design flexibility while enabling weight reduction due to topological optimisation. The quality and properties of the parts are strongly dependent on the powder quality which, in turn, is influenced by handling and storage of the powder. For this reasons an undefined contamination of atomised powder materials by oxygen and hydrogen has to be avoided. Aluminium-silicon powder was aged under atmosphere of different moistures and temperatures for defined duration. The effect of these environments as well as the effect of vacuum drying on the flowability was investigated. The morphology was evaluated by scanning electron microscope. The chemistry including oxygen content of the powder was measured by inductively coupled plasma optical emission spectrometry and hot fusion analysis.